A numerical investigation on multiaxial fatigue assessment of Nitinol peripheral endovascular devices with emphasis on load non-proportionality effects. (July 2019) - Berti, Francesca; Spagnoli, Andrea; Petrini, Lorenza
Highlights: The fatigue assessment in Nitinol stents is a multifactorial issue and requires deep investigation. The complex geometry and material type decouple the nature of the external load and the local response. The use of different fatigue criteria leads to discrepancies in the predictions. The critical plane approaches yield more realistic approximations. Abstract: This work first numerically investigates on the effect of the application of cyclic remote loads on the local stress/strain response of a peripheral stent. For this purpose, three stents of identical geometry, but different material properties (linear elastic, elastic-plastic and Nitinol material), were modelled and subjected to uniaxial and multiaxial proportional cyclic loads. The local response under uniaxial loads is non-proportional only for the case of Nitinol stent, while it happens for all the materials when multiaxial loads are applied. This paper also aims to evaluate how the use of different multiaxial fatigue criteria may affect the fatigue assessment for Nitinol peripheral stents. The same stent model was subjected to different proportional and non-proportional multiaxial cyclic loads and the results were interpreted using the standard von Mises and three approaches based on the concept of critical plane. The results showed that the von Mises is the most conservative criterion.